Synthesis, Crystal Structure of a Novel Two-Dimensional Complex of Manganese(II) with 2-Phenoxypropionic Acid and 4,4'-Bipyridine - Zhao, Guo-Liang; Liu, Jia-Lu (Asian Journal of Chemistry, 2012)
A novel two-dimensional coordination polymer [Mn(POPA)2(bipy)]n (POPA = 2-phenoxypropionic acid; bipy = 4,4'-bipyridine) has been synthesized by hydrothermal reaction and characterized by elemental analysis, IR spectroscopy, TGA and X-ray diffraction. Yellow crystals crystallized in monoclinic system, space group C2/c with a = 2.36748(14) nm, b = 1.16289(7) nm, c = 9.6440(6) nm, b = 96.353(4)º, V = 2.6388(3) nm3, Z = 4. In the complex, the manganese atom is six-coordinated with four carboxylic oxygen atoms from four 2-phenoxypropionic acid and two nitrogen atoms of two 4,4-bipyridine ligands, giving a octahedral geometry. CCDC:769183.